“There is No End”: Anna Akhmatova’s Unfinished Tragedy Prologue - Poberezkina, Polina (Literatūra, 2021)
The tragedy Prologue written in 1960s is analyzed in the broad context of the history of its creation, Anna Akhmatova’s biographical myth and world culture. The article mentions the problems of academic publication of the text and presents materials for scientific commentary on it. The incompleteness of the play is viewed in connection with its heterogeneous character combining lyrics, drama and epos, verses and prose, tragic and comic, ancient and modern, East and West, national and global, culture and everyday life, written and oral styles.
Keywords: Anna Akhmatova; East; incompleteness; subtext; written and oral styles